Effects of intrathecal dexmedetomidine on shivering after spinal anesthesia for cesarean section: a double-blind randomized clinical trial - Nasseri K; Ghadami N; Nouri B (Dove Medical Press, 2017)
Karim Nasseri,1,2 Negin Ghadami,1 Bijan Nouri2 1Department of Anesthesiology, Faculty of Medicine, Kurdistan University of Medical Sciences, Sanandaj, Iran; 2Social Determinants of Health Research Center, Kurdistan University of Medical Sciences, Sanandaj, Iran Background: Shivering is among the common troublesome complications of spinal anesthesia (SA), and causes discomfort and discontentment in parturients undergoing cesarean sections (CSs). The aim of this study was to investigate the effects of intrathecal dexmedetomidine in the prevention of shivering in those who underwent CS under SA.Subjects and methods: Fifty parturients planned for elective CSs under SA were enrolled in this prospective, double-blinded, controlled study and randomly divided into two equal groups. Spinal block was achieved with 12.5 mg 0.5% heavy bupivacaine plus 5 µg dexmedetomidine (BD group) or 0.5 mL 0.9% normal saline (BN group). The incidence and intensity of shivering, peripheral and core body temperature, hemodynamic parameters, and adverse events was recorded.Results: The incidence of shivering was significantly higher in the BN group (52%) than the BD group (24%) (P=0.04). Likewise, the intensity of shivering was significantly higher in the BN group than the BD group (P=0.04). The incidence of adverse events, such as hypotension, nausea/vomiting, and bradycardia, was not significantly different between the two groups, although the grade of sedation was higher in the BD group than the BN group (P=0.004).Conclusion: We conclude that intrathecal dexmedetomidine is effective in lowering the incidence and intensity of shivering in parturients undergoing CSs under SA without major adverse effects. Keywords: dexmedetomidine, shivering, spinal anesthesia, cesarean sections, bupivacaine